2015
DOI: 10.1080/24748668.2015.11868806
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Changing Player Numbers on the Physiological Responses and Time-motion Characteristics of a Soccer-Specific Training Drill

Abstract: Soccer-specific training (SST)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In addition, the studies by Abbott et al 28 , Beato et al 32 , Curtis et al 33 , Fitzpatrick et al 29 , Jaspers et al 34 , Knight et al 20 , Madison et al 19 , Rago et al 13 , Ramos et al 27 and Scott et and Lovell 2 presented some internal load monitoring. The studies by Fitzpatrick et al 26 , Madison et al 16 , and Scott and Lovell et al 2 used heart rate (HR) records as the only control of the internal load.…”
Section: Discussion and Implications For Practice And Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the studies by Abbott et al 28 , Beato et al 32 , Curtis et al 33 , Fitzpatrick et al 29 , Jaspers et al 34 , Knight et al 20 , Madison et al 19 , Rago et al 13 , Ramos et al 27 and Scott et and Lovell 2 presented some internal load monitoring. The studies by Fitzpatrick et al 26 , Madison et al 16 , and Scott and Lovell et al 2 used heart rate (HR) records as the only control of the internal load.…”
Section: Discussion and Implications For Practice And Researchmentioning
confidence: 99%
“…Thus, the studies demonstrated that 75% carried out their investigations based on training, with some studies occurring during the competitive period of the athletes, while 25% used official matches for data collection. None of these studies included data from goalkeepers, and the studies by Knight et al 20 and Trewin et al 18 did not limit the time taken to acquire GPS data for their studies.…”
Section: Description and Quality Of The Studiesmentioning
confidence: 99%